Role of Her-2/neu in Premalignant and Malignant Lesions of Uterine Cervix - SWASTI BAJPAI; SEEMA AWASTHI; SHYAMOLI DUTTA; ANKITA MITTAL; ASHUTOSH KUMAR; FAIYAZ AHMAD (Journal of Clinical and Diagnostic Research, 2017)
Introduction: In light of literature and controversy that exists in various cervical lesions, this prospective study was designed to explore the expression of Human Epidermal Growth Factor Receptor-2 (HER-2/neu) in the cervical lesions and its correlation with the histopathological grade and type of tumour. Immunohistochemistry (IHC) was performed to evaluate HER-2/ neu expression as it is the most reliable method of detecting overexpression of HER-2/neu. Aim: To assess the role of HER-2/neu expression in premalignant and malignant lesions of uterine cervix. Materials and Methods: Seventy cases of premalignant and malignant cervical lesions received in our department from January 2015 to December 2016, were included in study and Polyclonal Rabbit Anti-Human c-erbB-2 oncoprotein from DAKO was used. Standard streptovidin-biotin peroxidase method of IHC was followed. A golden brown membrane and cytoplasmic staining was taken as a positive reaction and intensity of expression was graded according to the 2014 ASCO/CAP guidelines for HER-2/neu reporting. Results: Out of total 70 cases, HER-2/neu expression scores were 0 in 64.3% {23 cases of Cervical Intraepithelial Neoplasia (CIN) and 22 of Squamous Cell Carcinoma (SCC)}, +1 in 22.9%, (04 cases of CIN and 12 of SCC) +2 in 10% (06 cases of SCC and 01 of adenosquamous carcinoma) and +3 in 2.9% (02 cases of adenocarcinoma) cases. HER-2/neu overexpression rate was significantly higher in malignant (48.8%) as compared to pre malignant (14.8%) cases (p=0.004) and expression scores were higher (+2 and +3) in 20.9% of malignant cases as compared to none of pre malignant cases (p=0.020). Significant higher HER-2/neu scores are seen (+2 and +3) in all the adenocarcinoma cases as compared to 15% cases of SCC (p<0.001). Among malignant cases, HER-2/neu expression was statistically significantly higher in {Moderately Differentiated (MD) + Poorly Differentiated (PD)} 59.09% as compared to {Well Differentiated (WD)} 38.09% cases (p=0.090). Conclusion: Study shows that expression of HER-2/neu is relatively lower in cervical lesions. However, the results of our study show that with shift from well to poorly differentiated lesions; the HER-2/neu expression rate shows an incremental trend.